Students’ conceptualizations of student hunger - Mansvelt, N.; Schenck, R.; Soji, Z. (South African Journal of Higher Education, 2022)
Student hunger and food-related challenges are a pressing issue for higher education institutions in South Africa and has a negative effect on academic success and overall student well-being. While recent studies focusing on student hunger have explored its prevalence and contributing factors quantitatively, little is known about students’ own views of the problem experienced by them and more specifically, about the ways in which students define or conceptualise hunger. This article about students’ conceptualisations of student hunger can aid institutions of higher education and other role players to plan interventions that are relevant and sustainable. Photovoice was employed with a group of students from one institution of higher education in South Africa. The students who volunteered to participate were from different study fields. From the collaborative data analysis process, two concepts emerged: hunger of the stomach and hunger of the mind. This finding highlights the complexity of addressing student hunger in ways that are comprehensive and sustainable.